EVALUATION STUDY ON GRADE 10 STUDENTS' UNDERSTANDING OF SEXUAL HARASSMENT AT SMAK KALAM KUDUS II - Patricia, Cindy; Hasan, Felix; Wandito, Jovan Giovanni; Suvena, Yenny; Wijaya, Vanness Dominique Nathan; Alvianto, Ravel; Anthonius, Ferdy; Sitepu, Eder Timanta (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2025)
The number of cases that occur is understood to be at a very concerning sexual level. This could be caused by a lack of understanding and knowledge about sexual thinking. Therefore, this study aims to analyze the level of knowledge and understanding of grade 10 students of SMA Kristen Kalam Kudus II about understanding sexuality to bring the issue of understanding sexuality to attention, help determine the next steps needed to increase student awareness of understanding sexuality and other sexual education, help achieve quality education in Indonesia, help reduce the number of cases of sexual enlightenment, and create a healthy and safe environment for the new generation. The research method used is a qualitative method using a semi-structured interview technique with 10 students randomly selected as respondents. Interview questions include basic understanding, identification of open sexual forms, and ways to prevent and report open incidents. Based on the results of the study, students of SMA Kristen Kalam Kudus II have a good level of knowledge about the definition and factors that cause sexual experiences, but understanding of the impacts and solutions still needs to be improved. Education on a more comprehensive understanding of sexuality and a safe and comfortable reporting system is needed to help students understand and deal with sexual problems better.